2020
DOI: 10.1007/s41669-019-00193-8
|View full text |Cite
|
Sign up to set email alerts
|

HSP27 Expression as a Novel Predictive Biomarker for Bevacizumab: is it Cost Effective?

Abstract: Background Despite the extensive use of bevacizumab in a range of oncology indications, the US FDA revoked its approval for breast cancers, and multiple negative trials in several solid malignancies have been reported, so the need for predictive biomarkers has increased. The development of predictive biomarkers for anti-angiogenic bevacizumab therapy has long been pursued but without success. Introduction Heat shock protein (HSP)-27 expression has recently been identified as a predictive biomarker for bevacizu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Thus, the EEs should incorporate the evidence of the test’s performance (or diagnostic accuracy) that result in a change in the management of subsequent therapeutic service. Also, it was observed from our previous empirical studies that the structure of comparing alternative strategies and choosing comparator strategy in EEs might lead to different cost-effectiveness results of their corresponding test-guided therapies and health outcomes [ 14 , 15 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the EEs should incorporate the evidence of the test’s performance (or diagnostic accuracy) that result in a change in the management of subsequent therapeutic service. Also, it was observed from our previous empirical studies that the structure of comparing alternative strategies and choosing comparator strategy in EEs might lead to different cost-effectiveness results of their corresponding test-guided therapies and health outcomes [ 14 , 15 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…This review of current practice with respect to the EE of companion biomarkers focuses on nine methodological areas. These key areas were formulated based on previous studies and existing HTA documentation guides on co-dependent technologies [2,3,[11][12][13][14][15], the Consolidated Health Economic Evaluation Reporting Standards (CHEERS) checklist [16]. We first used the framework of the CHEERS checklist and it provided useful information in formulating the key method areas for this review such as target population, study perspective, comparators, preference-based outcomes, and estimating resource use and costs.…”
Section: Data Analysis and Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The reference case applied in this worked example of the core model is summarized in Table 1 . This core model is developed based on the findings and practical lessons acquired from previous studies on companion diagnostics or co-dependent technologies [ 8 , 10 , 16 , 17 ]. Systematic reviews found that the characteristics of companion biomarker tests were not consistently incorporated in economic evaluations of biomarker-guided therapies and the structure of comparative analyses of the strategy arms was so varied that it may lead to a different conclusion in terms of cost effectiveness [ 8 , 10 , 17 ].…”
Section: Model Background and Descriptionmentioning
confidence: 99%
“…Instead, they compared biomarker-guided therapy with biomarker testing versus without the testing, while no SOC was considered in the evaluations. Therefore, based on the study findings from previous studies [ 8 , 10 , 16 ], we found that assessing the biomarker-guided therapy against two comparator strategies was the most suitable structure for strategy comparison. Therefore, we constructed three strategies as default comparisons in this core model: (1) patients being tested with a companion biomarker and treated with the corresponding targeted therapy according to their biomarker testing result (hereinafter referred to as the test–treat strategy, i.e.…”
Section: Model Background and Descriptionmentioning
confidence: 99%